The dopaminergic neuroprotective effects of different phytosterols identified in rice bran and rice bran oil. Issue 21 (27th September 2021) - Zhang, Jiali; Zhang, Lu; Wu, Zhengzhang; Zhang, Peng; Liu, Ruijie; Chang, Ming; Wang, Xingguo
Abstract : Phytosterols are important bioactive compounds in rice bran and rice bran oil, and the compositions of different phytosterols in rice bran and rice bran oil were investigated in our previous research. Abstract : Phytosterols are important bioactive compounds in rice bran and rice bran oil, and the compositions of different phytosterols in rice bran and rice bran oil were investigated in our previous research. In this study, the dopaminergic neuroprotective effects and the underlying mechanisms of sitosterol, cycloartenyl ferulate, 24-methylenecycloartanyl ferulate and campesteryl ferulate identified in rice bran and rice bran oil were investigated in a rotenone-treated C. elegans model. The results indicated that the increased oxidative stress resistance induced by the activation of the DAF-16/FOXO pathway and the inhibition of the apoptotic protein CED-3 overexpression might play an important role in protecting the dopaminergic neurons. The results of this research reveal a new bioactivity of different phytosterols and are helpful for the further nutritional evaluation of rice bran and rice bran oil.